Institutional pathways for enhancing villagers’ participation in rural human settlement governance amid collective action dilemmas: using NCA and fsQCA approaches - Xin Nie; Li Qiu; Tianci Wu; Xiaoyu Yang; Fengqin Li; Wenhan Feng; Han Wang (Environmental Research Communications, 2025)
In rural human settlement governance, the conflict between the demands of collective rationality and villagers’ individual rational pursuits often leads to collective action dilemmas of governance. Drawing on Ostrom’s eight institutional design principles (DPs), this study employs a hybrid methodology combining Necessary Condition Analysis (NCA) and fuzzy-set Qualitative Comparative Analysis (fsQCA) to systematically examine how institutional arrangements influence villagers’ participation in rural human settlement governance from a holistic institutional perspective, while exploring institutional pathways for overcoming problems of collective action. Key findings are: (1) four effective pathways for enhancing villagers’ participation and curbing free-riding behavior: the institutional supply-led model, implementation-recognition model, safeguards-supervision model, and multi-dimensional co-governance approach; (2) core institutional principles enabling active participation: clearly defined boundaries (DP1), congruence between the rules and local conditions (DP2), and conflict-resolution mechanisms (DP6); (3) these institutional principles demonstrate both substitutional and complementary relationships across different pathways, and their strategic utilization can effectively constrain and incentivize villagers to align their individual actions with collective interests. This study concludes that resolving collective action dilemmas requires the synergistic integration of institutional advantages, establishing an operational logic that facilitates positive interactions among multiple stakeholders. This study deepens our understanding of institutional roles in rural habitat governance, widens the exploration of institutional pathways for problems of collective action, and provides practical implications for modernizing rural environmental governance systems and capabilities.